Rathke’s Cleft Cyst Abscess—An Unusual Guest in The Sella - Lodha, Piyush; Srinivas, P Rao; Danda, Vijay Sheker Reddy; Rao, Gollapudi Prakash (Indian Journal of Neurosurgery, 2021)
Abscess formation within a Rathke's cleft cyst (RCC) is extremely rare, particularly at a young age. We report the case of a young girl with abscess formation in RCC. A 21-year-old female presented with headache, vomiting, visual deterioration and features suggestive of hypopituitarism. She had bitemporal hemianopia with impairment of visual acuity. MRI revealed a cystic lesion in the sella with suprasellar extension and peripheral rim enhancement. On the basis of history and imaging, this was indistinguishable from more commonly encountered pituitary pathology. She underwent transsphenoidal decompression, which revealed yellowish purulent material that when cultured grew Staphylococcus epidermidis. Histological examination revealed numerous neutrophils and cyst wall lining with features characteristic of RCC. Postoperatively, she received antibiotics and replacement therapy for hypopituitarism. Three months later, she experienced deterioration in visual fields. Considering persistent disease, she underwent redo surgery which revealed similar findings. Postsurgery, pituitary MRI revealed an empty sella syndrome. Thereafter, follow-up for 1 year was stable with permanent diabetes insipidus and multiple pituitary hormone deficiency on supplementation. Although uncommon, we recommend considering RCC abscess as a differential diagnosis of a pituitary mass lesion, as predicting its presence can be difficult preoperatively. Persistent or recurrent disease is common in these cases, so timely diagnosis and adequate surgical drainage leads to lower morbidity and mortality.
Keywords: Rathke’s cleft cyst abscess; pituitary mass lesion; endoscopic transsphenoidal resection